“My Name is Peaches”: Literature, Lyrical Activism and Black Music - Gillett, Rachel Anne (FRAME, Journal of Literary Studies, 2026)
This article explores how one might conceptualise music as a form of literary activism. It close reads naming, witnessing, metaphor, allusion, and calls-toaction in the three songs “Four Women” by Nina Simone, “Strange Fruit” by Billie Holiday, and “Glory” by John Legend and Common. These close readings demonstrate how we might consider lyrical activism in music as a form of literary activism. It argues that song forms can be literature and contribute to an aesthetic treasure trove of literature that works upon readers, and upon the world, in an active intentional way, to achieve social change. The essay also provokes the question of the bounds of the literary and the musical.